Analysis of the effect of the promotion mix on room revenue at the Malang Tidar Tourism Hotel - L. Seno Bayu Putro (Central Research Institute for Agriculture (CeRIA), 2021)
The purpose of this research is to determine the effect of the promotion mix on room revenue and to find out which promotion mix has the most dominant effect on room revenue. This research is expected to be useful for the authors, the Hotel Wisata Tidar, and other competent parties. The results showed that only the personal selling variable had a very significant effect on room income, while the advertising variable had a less significant effect on room income, so this variable was omitted (due to multicollinearity symptoms). The development of Indonesia's tourism world continues to increase from time to time which can be seen from indications of an increasing number of tourists visiting tourist destinations in Indonesia, which are famous for their natural beauty, friendliness of the people, and cultural diversity. Along with these developments, many hotel businesses that provide lodging services and other supporting services have sprung up. Hotel Wisata Tidar as one of the hotels in the city of Malang, also takes part in the development of the hospitality business in Indonesia. In carrying out its operations, Hotel Wisata Tidar also tries to compete as optimally as possible, even though it is still a newcomer. In an effort to promote itself, Hotel Wisata Tidar uses 2 (two) promotional mix media, namely: advertising and personal selling. Based on the above, to find out how far the effectiveness of promotional activities carried out in relation to room revenue earned, this research was conducted. The variables used in this study consisted of 2 (two) variables, namely: the independent variable (advertising and personal selling) and the dependent variable (room income).